2023
DOI: 10.1002/ase.2245
|View full text |Cite
|
Sign up to set email alerts
|

The gross anatomy course:SARS‐CoV‐2 pandemic‐related effects on students' learning, interest in peer‐teaching, and students' perception of its importance

Abstract: The COVID‐19 pandemic required adjustments and limitations in university teaching, thereby challenging teaching concepts in anatomy requiring in‐person contact, including the gross anatomy course. Therefore, the present study investigates the impact of COVID‐19‐associated adjustments on students' perception of the gross anatomy course's importance and quality, students' preferred learning setting and outcome, and their motivation to involve themselves in academic activities, including becoming a future peer‐te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…With the shift to online education because of the pandemic, medical students have been deprived of access to cadavers, which have traditionally been the principal method of learning anatomy. 3 As a result, there has been a growing need to explore virtual/ digital alternative techniques. 4 Several authors have found 3D models to be a beneficial tool in medical education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the shift to online education because of the pandemic, medical students have been deprived of access to cadavers, which have traditionally been the principal method of learning anatomy. 3 As a result, there has been a growing need to explore virtual/ digital alternative techniques. 4 Several authors have found 3D models to be a beneficial tool in medical education.…”
Section: Discussionmentioning
confidence: 99%
“…2 Especially during the coronavirus disease 2019 (COVID-19) pandemic, when face-to-face education was disrupted, the use of these technologies, especially in anatomy, gained significant importance in distance education. 3,4 The initial step in utilizing these technologies is the…”
mentioning
confidence: 99%